(untitled) (International Journal of Engineering and Computer Science, 2017)
Early we use Plain Textual passwords as a security. A password is a word or string of characters used for user authentication. A typical computer user has passwords for many purposes: logging into accounts, retrieving e-mail, accessing applications, networks, web sites, and reading the newspapers online. The common method which we used is a Textual password which is lengthy and consider as secured but difficult to remember thus the user pick short password but short password are easily crack or hack. A fundamental task in security is to create cryptographic primitives based on hard mathematical problems that are computationally intractable for security, initially proposed, is an exciting new paradigm. So we proposed new password authentication technique is Session password and color password. Where it gives the options for user to select the password as a color or alphanumerical grid.